O3-S2.05 Prevalence of Trichomonas vaginalis and co-infection with Chlamydia trachomatis and Neisseria gonorrhoea in the USA as determined by the APTIMA Trichomonas vaginalis nucleic acid amplification assay. (10th July 2011) - Ginocchio, C C; Chapin, K; Smith, J S; Aslanzadeh, J; Snook, J; Hill, C S; Gaydos, C A
Abstract : Background: Trichomonas vaginalis (TV) is the most common curable sexually transmitted infection worldwide. True prevalence of TV infection is not well characterised as previous studies mainly used methods with relatively poor sensitivity compared to nucleic acid amplification methods. Our aim was to determine TV prevalence using the APTIMA TV Assay (ATV, Gen-Probe Incorporated) and the frequency of co-infections with Chlamydia trachomatis (CT) and Neisseria gonorrhoea (NG) in the USA among women being screened. Methods: Samples from 7593 women aged 18–89 years undergoing routine CT and NG screening at obstetrics/gynaecology, emergency room, hospital in-patient, family practice, family planning, internal medicine, jail, and STD clinic populations in 21 states were collected. Consecutive samples previously tested for CT and NG by the APTIMA COMBO 2 Assay (Gen-Probe Incorporated) were retrospectively tested with the ATV assay. Endocervical, urine, vaginal swab and PreservCyt liquid Pap samples (Hologic Inc.) diluted into APTIMA specimen transport buffer were tested. Results: Overall prevalences of TV, CT and NG in surveyed women were 8.7%, 6.7%, and 1.7%, respectively. TV prevalence ranged from 7.5 to 8.6% in women age 18 to 39 yr, and increased to 9.8% in women age 40–44 yr. Highest observed TV prevalences were in women ages 45–49 yr (13.4%) and over 50 yr (13.0%). CT and NG prevalences were less than 2% in the 40+ age group and highest in women less than 30 years of age ranging from 5.2% to 14.3% for CT and 1.3%–3.3% for NG. TV was the more prevalent STD than either CT or NG in all age groups, except the 18-19 yr group (CT: 14.3%; TV: 8.5%). TV prevalence differed by race/ethnicity (20.2% blacks; 5.7% whites; 5.0% Hispanics; 3.8% Asians). TV prevalence was 14.4% in the Southeast, 9.5% in the Southwest and Midwest, and 4.3% in the Northeast and ranged from 5.4% in Family Planning clinics to 22.3% in jails. Co-infections in most age groups were <1%, and were highest in the 18–19 yr group (TV/CT: 2.1%; TV/NG: 0.88%). Conclusions: TV prevalence was highest in women over 40 years of age, in contrast to CT and NG prevalences which were highest in women under 30 years of age. Co-infection of TV with CT or NG was relatively low. The high TV prevalence in all age groups suggests that all women being screened for CT/NG should also be screened for TV. Routine TV screening should also be considered for at-risk sexually active women of any age.